2020
DOI: 10.3390/ani10010170
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Study of Body Weight Traits in Chinese Fine-Wool Sheep

Abstract: Body weight is an important economic trait for sheep and it is vital for their successful production and breeding. Therefore, identifying the genomic regions and biological pathways that contribute to understanding variability in body weight traits is significant for selection purposes. In this study, the genome-wide associations of birth, weaning, yearling, and adult weights of 460 fine-wool sheep were determined using resequencing technology. The results showed that 113 single nucleotide polymorphisms (SNPs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 52 publications
(45 reference statements)
3
47
0
Order By: Relevance
“…The QTL regions and the genes: ADAMTSL3, CAPN2, CAPN2, FABP6, ZEB2 were detected using GWAS in Colombian Brahman cattle that in uencing growth and weight traits 37 . Lu et al 11 (2020) reported SLCO2A1, LY6K, RALYL, AADACL3, C17H4orf45, BICC1, SHROOM2 as candidate genes for birth weight in Chinese Fine-Wool Sheep 11 . The candidate genes for Dry Matter Intake, Average Daily Gain, and Metabolic Body Weight based on the imputed 7.8 M WGS in chattels were reported: SNORA70, B3GALT1, DDR2, GPR37, SYT1, LYZL1, RGS2, F13A1, SNORA31, LCORL, DPH6, PARD3, MOS, CRB1, CUL1, CCND2, ARRDC3, PLAG1, STC2, CARD11, TMEM72, SCGB1A1, ERICH6, ARRDC3, GALNT14, PLAG1, ERGIC1, AP3S2, A1CF 38 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The QTL regions and the genes: ADAMTSL3, CAPN2, CAPN2, FABP6, ZEB2 were detected using GWAS in Colombian Brahman cattle that in uencing growth and weight traits 37 . Lu et al 11 (2020) reported SLCO2A1, LY6K, RALYL, AADACL3, C17H4orf45, BICC1, SHROOM2 as candidate genes for birth weight in Chinese Fine-Wool Sheep 11 . The candidate genes for Dry Matter Intake, Average Daily Gain, and Metabolic Body Weight based on the imputed 7.8 M WGS in chattels were reported: SNORA70, B3GALT1, DDR2, GPR37, SYT1, LYZL1, RGS2, F13A1, SNORA31, LCORL, DPH6, PARD3, MOS, CRB1, CUL1, CCND2, ARRDC3, PLAG1, STC2, CARD11, TMEM72, SCGB1A1, ERICH6, ARRDC3, GALNT14, PLAG1, ERGIC1, AP3S2, A1CF 38 .…”
Section: Discussionmentioning
confidence: 99%
“…A number of 28 SNPs were found to be associated with birth weight, daily gain, and body weight of dromedaries (p value < 0.001) ( Table 4). For birth weight, 12 correlated SNPs (p value < 0.001) were detected on the chromosomes 7,8,9,11,19, and 34 were annotated to 9 genes (Table 4). For daily gain, 7 correlated SNPs (p value < 0.001) on the chromosomes 10, 16, 12, 19, and 14, were annotated to 11 genes (Table 4).…”
Section: Genome Wide Association Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Human pathologies in this gene lead to mucopolysaccharidosis type I, which presents a global phenotype that includes coarse hair (Scott et al ., 1995; Kloska et al ., 2005). Furthermore, an alternative allele of GLIS1 , an enhancer of pluripotency markers (Maekawa et al ., 2011), and the reference allele of AADACL3 , which is associated with fat deposition in Chinese sheep breeds (Lu et al ., 2020), were found in the regions under selection with support from F ST . The reference allele of GPR179 , highlighted by H1 / H2 statistics, which is linked to genetic blindness, was also found under selection in Tuva sheep (Audo et al ., 2012).…”
Section: Figurementioning
confidence: 92%
“…The availability of reference genome assemblies coupled with GBS enables us to explore in greater detail of dromedary populations and to identify genetic associations with different phenotypic traits 10 . Genome-wide association studies (GWAS) are used to screen the whole genome for target genes that correlate with phenotypic traits, using SNPs and an important method for identifying candidate genes for important economic traits in livestock 11 . GWAS have a greater capability than QTL mapping to detect causal SNPs in a smaller genetic range 12 .…”
Section: Introductionmentioning
confidence: 99%